The Helmand Baluch : a native ethnography of the people of southwest Afghanistan - Amīrī, Ghulām Raḥmān (Berghahn Books, 2021)
"This rich ethnography describes the cultural, political, and economic systems of the Baluch people living in the lower Helmand River Valley of Afghanistan. It is an area that has received little study since the early 20th Century, yet is a region with a remarkable history in one of the most volatile territories in the world"--